Morphohistogenesis of oesophagus in fowl (Gallus aomesticus) - VERMA, D; MALIK, M R; PARMAR, M L; TALUJA, J S (The Indian Journal of Animal Sciences, 2013)
Oesophagus extended from pharynx to pro_ventriCulus in right side of the neck. It had 2 parts, pre-crop and post-crop. The pre-crop part was longer (9.80-65.00 mm) and wider (1 72-14.00 mm) than the post-crop (7.70-50.00 rum) and (1.6813.20 mm) in all the age groups. The CS area pre-crOP was more than post-crop in all the age groups except groups 8 and 10 where it was more in post-crop The growth spurt: of length and width of both the parts revealed maximum (85 18 and 46.66%, 132.55 and 90.40%) increase in groups 3.A and 2-3 respectively. However, CS area revealed maximum and minimum values of growth spurt in groups 4 onwardÂ· The overall mean thickness of the wall of post-crop part (1201.40 mm) was more than that of the preÂ· crop (1172.80 um). The tunica mucosa of both the parts of oesophaifrus on an average contributed approximately double (46.40-67.49%) than tunica muscularis (29.00-44.59%). The epithebtnn changed from simple cuboidal (group 2) to stratified squamous (group 4). The villi and oesophageal glands appeareJ in group 3. In groups 4 onward, the cells of the superficial layer of epithelium in post-crop part were keratinized, However, keratinization was not conspicuous in pte-crop. The tubuloalveofar mucous glands in post-crop were profuse in the mucosal folds in contrast to uniformly distributed in the pre-crop.